Inhibition of myotube formation by platelet-derived growth factor subunit B in QM7 cells - Sarang Choi; Sangsu Shin (Animal Bioscience)
Objective The primary objective of this study was to investigate the role and regulatory mechanisms of platelet-derived growth factor subunit B (PDGFB) in muscle differentiation. Methods In this study, a vector for PDGFB was designed and transfected into quail muscle cells to investigate its role and regulatory mechanism during muscle formation. To investigate the inhibitory mechanisms of PDGFB on myogenic differentiation, the mRNA expression levels of various genes and the phosphorylation of extracellular signal-regulated kinase 1/2 (ERK 1/2), both known to regulate muscle development and differentiation were compared. Results PDGFB-overexpressed (OE) cells formed morphologically shorter and thinner myotubes and demonstrated a smaller total myotube area than did the control cells. This result was also confirmed at the molecular level by a reduced amount of myosin heavy chain protein in the PDGFB-OE cells. Therefore, PDGFB inhibits the differentiation of muscle cells. Additionally, the expression of myogenin (MYOG) significantly decreased in the PDGFB-OE cells on days 2 and 4 compared with that in the control cells. The phosphorylation of ERK 1/2, an upstream protein that inhibits MYOG expression, increased in the PDGFB-OE cells on day 4 compared with that in the control cells. The decreased expression of MYOG in the PDGFB-OE cells increased by inhibition ERK 1/2 phosphorylation. Conclusion PDGFB may suppress myogenesis by reducing MYOG expression through ERK 1/2 phosphorylation. These findings can help understand muscle differentiation and potentially improve poultry meat production.